Human Nature, Ritual, and History : Studies in Xunzi and Chinese Philosophy (Studies in Philosophy and the History of Philosophy, Volume 43) - Cua, A. S. (Antonio S.), 1932-2007 (Book collections on Project MUSE., 2005)
"In this volume, distinguished philosopher Antonio S. Cua offers a collection of original studies on Xunzi, a leading classical Confucian thinker, and on other aspects of Chinese philosophy. While each essay individually makes an important contribution to the study of Chinese philosophy, the book as a whole represents a major scholarly achievement."--Jacket